STRUCTURAL ANALYSIS AND EXPRESSIVE SPEECH ACTIONS OF THE DRAMA SCRIPT “SUDAH GILA” BY CHAIRIL ANWAR - Ai Cahyani; Wita Adia Amelia; Galih Ahmad Rivaldi; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Drama has become a mirror of human life, creating narratives that enrich our understanding of human existence. This article explains basic concepts in the world of drama, along with important approaches in studying literary works such as structural and expressive. The structural approach helps us understand the formal elements of drama that interact with each other to form a cohesive narrative, while the expressive approach allows us to explore layers of emotions and character motivations which also discusses expressive speech acts, which are the use of language in drama to convey messages and emotions. Through exploring these concepts, we can deepen our experience in understanding and appreciating dramatic works, as well as reflecting on the human essence revealed on the stage of life. The data source for the study using a structural and expressive approach to speech acts in this research is the drama script Jadi Gila by Chairil Anwar by analyzing each dialogue of the characters. The method used is descriptive qualitative. Data collection techniques use reading, note-taking and literature study techniques. Meanwhile, the technique for analyzing data uses content analysis.